Pelas f(r)estas da cidade: práticas espaciais urbanas no contexto da Atenção Psicossocial de Fortaleza - Dantas, João Gabriel Trajano (Universidade Federal de São Carlos, 2025)
The consolidation of Psychosocial Care in Brazil highlights the relationship with territory and community as a guiding principle for the operation of services and the production of mental health care for the population. This aspect encourages the development of practices that transcend institutional walls, gaining color, rhythm, meaning, and dialogue within various urban spaces. It is within this context that the central question of this thesis emerges: how can practices mediated by artistic and cultural experiences, carried out in urban public spaces, contribute to the production of cracks (f(r)estas) that celebrate the principles of citizenship, inclusion, sociocultural participation, belonging, diversity, and mental health care? To engage with this question, we adopted a qualitative and exploratory research-intervention methodology, grounded in a cartographic perspective. The objective is to analyze the production of mental health and the occupation of urban public spaces through the cartography of experiences lived in the city of Fortaleza, Ceará, Brazil. The investigation was conducted mainly from the perspective of professionals and service users regarding the daily work within Psychosocial Care, as well as through the procedural follow-up of two experiences: the traditional carnival group ‘Doido é Tu’ (BDT) and the II Mad Pride Parade, an event related to the Anti-Asylum Campaing Day. The results are presented through three pathways: the historical-political dimension; the molecular or everyday dimension of work in Psychosocial Care; and the sociocultural dimension of urban practices and their interface with care. The investigative journey contributes to the field by proposing the notion of f(r)estas, through an articulation between mental health, art, and culture in the city. It concludes that urban spatial practices can function both as analyzers of management and care models in mental health and as conditions and effects of clinical practices committed to social emancipation. The production of f(r)estas arises from the collective construction of spaces of joy, celebration, and festivity, reclaiming urban daily life for the diversity of ways of living, citizenship, cultural practices, and belonging, as well as for the exercise and defense of the right to care in freedom.

La consolidación de la Atención Psicosocial en Brasil destaca la relación con el territorio y la comunidad como una directriz fundamental para el funcionamiento de los servicios y para la producción del cuidado en salud mental de la población. Este aspecto favorece la instauración de prácticas que trascienden los muros institucionales, ganando color, ritmo, sentido y diálogo en diferentes espacios urbanos. Es en este contexto que surge la cuestión que orientó el recorrido de esta tesis: ¿cómo pueden las prácticas mediadas por experiencias artísticas y culturales, realizadas en espacios públicos urbanos, contribuir a la producción de fisuras (f(r)estas) que celebren los principios de ciudadanía, inclusión, participación sociocultural, pertenencia, diversidad y cuidado en salud mental? Para dialogar con esta cuestión, partimos de una metodología de investigación-intervención cualitativa y exploratoria, ubicada dentro de una perspectiva cartográfica. El objetivo es analizar la producción de salud mental y la ocupación de espacios públicos urbanos mediante la cartografía de experiencias vividas en la ciudad de Fortaleza, Ceará, Brasil. La investigación se desarrolló especialmente a partir de la perspectiva de profesionales y usuarios sobre el cotidiano del trabajo en la Atención Psicosocial y del acompañamiento procesual de dos experiencias: el tradicional bloco carnavalesco ‘Doido é Tu’ (BDT) y la II Marcha del Orgullo Loco, evento alusivo al Día de la Lucha Antimanicomial. Los resultados se presentan a partir de tres recorridos: la dimensión histórico-política; la dimensión molecular o cotidiana del trabajo en la Atención Psicosocial; y la dimensión sociocultural de las prácticas urbanas en su interfaz con el cuidado. El recorrido investigativo aporta al campo la noción de f(r)estas, articulando salud mental, arte y cultura en la ciudad. Se concluye que las prácticas espaciales urbanas pueden funcionar como analizadores de los modelos de gestión y de cuidado en salud mental y, al mismo tiempo, como condición y efecto de prácticas clínicas comprometidas con la emancipación social. La producción de f(r)estas surge de la construcción colectiva de espacios de alegría, celebración y fiesta, reivindicando para la vida urbana cotidiana la diversidad de modos de vida, ciudadanía, prácticas culturales y de pertenencia, así como el ejercicio y la defensa del derecho a un cuidado en libertad.
Through the (s)lits of the city: urban spatial practices in the context of psychosocial care in Fortaleza
Por las gr(f)ie(s)tas de la ciudad: prácticas espaciales urbanas en el contexto de la atención psicosocial en Fortaleza
Keywords: Atenção psicossocial; Cidades; Espaço urbano; Luta antimanicomial; Arte e cultura; Terapia ocupacional; Carnaval; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL